Intertextual relations between the text of parody and the precedental text - Savchenko (Chuprina), N.N. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2011)
The article specifies the basic contacts between the text of parody and the precedental text in the single text space. The forms of intertextuality (intertexts) are presented as allusions, quotations, reminiscences that are combined and create the original implications in the text of parody. The role of appealing function of the text of parody has been determined. The latter is considererd as a play text. Due to that the recipient (anthropocentre) for whom the text of parody and the precedental text are created can adequately grasp the information.
Keywords: the text of parody; the precedental text; intertextuality; intertext; implication; recipient